Genome-wide association mapping of vitamins B1 and B2 in common wheat - Jieyun Li; Jindong Liu; Wei'e Wen; Pingzhi Zhang; Yingxiu Wan; Xianchun Xia; Yan Zhang; Zhonghu He (Crop Journal, 2018)
Vitamin B is essential for maintaining normal life activities in humans and animals who have to intake the microelement from the outside, especially from cereal products. In the present study 166 Chinese and foreign wheat cultivars planted in two environments were characterized for variation in vitamin B1 and B2 contents. A genome-wide association study (GWAS) using the wheat 90 K SNP assay identified 17 loci for vitamin B1 and 7 for vitamin B2 contents. Linear regression analysis showed a significantly positive correlation of the number of favorable alleles with vitamin B1 and B2 contents. Marker-trait associations (MTAs) at IWB43809 (6AS, 0 cM) and IWB69903 (6AS, 13 cM) were new and stable, and significantly associated with vitamin B1 content across two environments. The loci identified in this study and associated SNP markers could be used for improvement of vitamin B1 and B2 contents to obtain superior quality along with grain yield in wheat. Keywords: 90 K SNP assay, GWAS, Vitamin B1, Vitamin B2, Triticum aestivum